INTERNET ADDITICTION DISORDER SEBAGAI SALAH SATU TENDENSI CACAT KESEPAKATAN NIKAH (Studi Kasus Dalam Terang Hukum Perkawinan Katolik Kanon 1095) - Yoesi Prasetya Nada (Aggiornamento, 2022)
This article discusses an idea regarding the phenomenon of IAD (internet addiction disorder) which is currently developing and its relation to marriage agreements according to the norms of Catholic Marriage Law, especially those based on canon 1095. To arrive at a clear point of continuity between this phenomenon and the marriage law of the Catholic Church , this article first formulates the definition and development of IAD, formulates the content of the idea can. 1095 and looking for a relationship from the two. The context that is being faced together is the concern about the rise of IAD cases in Indonesia in the midst of the times, especially in this millennial era. So the subject of writing this article is everyone who decides to decide on a marriage, but the person concerned has an IAD disorder. The focus of this study is application. 1095 in the context of today's digital world; where there is a danger of IAD that threatens the current generation. In writing, this article uses a qualitative methodology with literature studies and previous studies as the instrument. The aim of this study is to understand the development situation and the adverse effects of today's lifestyle. The relevance of this writing is the right and wise judgment in deciding a marriage case that has a background in the IAD phenomenon